Observer variability in histopathological reporting of malignant bronchial biopsy specimens. Issue 8 (August 1994) - Burnett, R A; Swanson Beck, J; Howatson, S R; Lee, F D; Lessells, A M; McLaren, K M; Ogston, S; Robertson, A J; Simpson, J G; Smith, G D
Abstract : AIMS–To evaluate the ability of histopathologists to classify lung carcinomas on bronchial biopsy material using the current World Health Organisation (WHO) classification. METHODS–Eleven histopathologists each reviewed 100 randomly selected bronchial biopsy specimens which had originally been reported as showing lung carcinoma. A single haematoxylin and eosin stained section from each case was circulated and a standard proforma completed. These were analysed using kappa statistics. RESULTS–The histopathologists were excellent at distinguishing between small cell and non-small-cell carcinoma kappa = 0.86), but not so good at subclassifying the non-small cell carcinoma group kappa = 0.25). CONCLUSIONS–The clinically important distinction between small cell and non-small cell carcinoma of the lung is reliably made by competent histopathologists even on limited material.